REDUCTION OF TSS AND COD IN RESTAURANT WASTEWATER USING NATURAL COAGULANT FROM KEPOK BANANA PEEL POWDER - Mutiara Fajar; Iis Mulyani; Andika Munandar (JURNAL INTEGRASI PROSES, 2024)
Wastewater from restaurant activities contains organic compounds such as carbohydrates, proteins, fats, and oils that can pollute and damage the environment. Therefore, further research is needed to prevent this pollution. This study aims to analyse the characteristics of restaurant wastewater and utilise kapok banana peel waste as a natural coagulant to reduce TSS (total suspended solid) and COD (chemical oxygen demand) concentrations in the wastewater. Additionally, this study aims to analyse the correlation between the reduction in TSS and COD concentrations after the coagulation process. The results showed that kapok banana peel powder has polyelectronic properties and contains carboxyl, hydroxyl, and amide groups acting as active components in the coagulation-flocculation process. The coagulation-flocculation process was efficient at 400 mg biocoagulant, with reduction efficiencies of 92% for TSS and 73% for COD. Based on Pearson correlation analysis using SPSS, the reduction in TSS and COD concentrations had a very strong (r=0.954) and significant (Sig.=0.000) relationship.